Natural Killer Defective Maturation Is Associated with Adverse Clinical Outcome in Patients with Acute Myeloid Leukemia - Chretien, Anne-Sophie; Fauriat, Cyril; Orlanducci, Florence; Galseran, Claire; Rey, Jerome; Bouvier Borg, Gaelle; Gautherot, Emmanuel; Granjeaud, Samuel; Hamel-Broza, Jean-François; Demerle, Clemence; Ifrah, Norbert; Lacombe, Catherine; et al. (Frontiers in Immunology, 2017)
Accumulating evidence highlights NK cell parameters as potential prognostic factors in cancer patients, which provides a strong rationale for developing therapeutic strategies aiming at restoring NK cell. However, reaching this point warrants better characterization of tumor-induced NK cell alterations. Our group recently reported heterogeneous NK maturation in AML patients. However, the clinical significance of such observations remained to be assessed on a larger cohort of patients. NK maturation based on expression of CD56, CD57 and KIR was assessed by flow cytometry in newly-diagnosed AML patients (N=87 patients from GOELAMS-LAM-IR-2006 multicenter trial). Clinical outcome was evaluated with regard to NK maturation profiles. Unsupervised integrated analysis of NK maturation markers confirmed the existence of three distinct groups of patients (hypomaturation (24.1%), intermediate maturation (66.7%) and hypermaturation (9.2%)). In univariate analysis, significant differences in overall survival (OS) (P=0.0006) and relapse-free survival (RFS) (P<0.0001) were observed among these different groups. Patients with hypomaturation profile had reduced OS, with 3-year OS rates of 12.5% vs 57.1% and 57.4% for patients with intermediate and hypermaturation, respectively. Consistently, patients with hypomaturation profile had reduced RFS, with 3-year RFS rates of 0% vs 52.6% and 73.3% for patients with intermediate and hypermaturation, respectively. In multivariate Cox regression models, NK hypomaturation remained significantly associated with reduced OS and RFS, independent of other factors (HR (hazard ratio)=4.15, P=0.004 and HR=8.23, P=0.003, respectively). NK maturation defects were further explored by mass cytometry, and revealed that NK hypomaturation profile is associated with a reduced frequency of memory-like NK cells. In conclusion, beside classical alterations of NK triggering and inhibitory receptors expression in AML, we confirm that the homeostasis of NK maturation can be modified in the context of AML, notably with a deep maturation blockade in almost 10% patients.